2014
DOI: 10.3324/haematol.2013.100230
|View full text |Cite
|
Sign up to set email alerts
|

SIGLEC-G deficiency increases susceptibility to develop B-cell lymphoproliferative disorders

Abstract: The sialic-acid-binding immunoglobulin-like lectin SIGLEC-G is a negative regulator of B-cell receptor-mediated calcium signaling. Its deficiency leads to reduced turnover and increased proliferation and survival of murine B-1a cells. Siglecg −/− mice show a premature expansion of polyclonal CD5 + B cells in the spleen and the peritoneal cavity. Here we studied the fate of B lymphocytes in Siglecg −/− mice over time. We demonstrate that in aging animals SIGLEC-G deficiency promotes progressive accumulation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Several recent reports suggest that siglec deficiencies can increase the potential for generation of lymphomas and leukemias 107, 108 . Moreover, in keeping with their roles aiding immune cells in distinguishing between self and non-self, Siglecs are emerging as playing a role in regulation of immune surveillance of cancer.…”
Section: Siglecs In Immune Surveillance Of Cancermentioning
confidence: 99%
“…Several recent reports suggest that siglec deficiencies can increase the potential for generation of lymphomas and leukemias 107, 108 . Moreover, in keeping with their roles aiding immune cells in distinguishing between self and non-self, Siglecs are emerging as playing a role in regulation of immune surveillance of cancer.…”
Section: Siglecs In Immune Surveillance Of Cancermentioning
confidence: 99%
“…These aMyIIA B1a cells ultimately transformed into malignant cells with the characteristic of mature cells, with decreased Siglec-G expression ( Figure 6I ). The reduced Siglec-G expression may contribute to pathogenesis, since Siglec-G deficiency increases B-cell lymphoproliferative disorders ( 46 ). Thus, the increased Arid3a in Lin28b + Let7 − outcome at the pre-B cell stage allowed the generation of SLC-unassociated autoreactive BCR B1a cells from adult BM, and ultimately support the ability to develop B1a cell tumors (summarized in Figure 6J ).…”
Section: Resultsmentioning
confidence: 99%
“…In our analysis, we found that all siglecs including siglec-1 to siglec-9 were significantly suppressed in HCC tumors, which may serve as anti-oncogenes. Recently, several studies revealed that siglec deficiencies contributed to the potential for generation of malignancy like lymphomas and leukemias [ 17 , 18 ]. As reviewed by Macauley et al, siglecs played a role in regulating of immune surveillance of cancer by keeping with their roles aiding immune cells in distinguishing between self and non-self [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Siglecs including siglec-2 have been reported to regulate cell growth and survival, by both inhibition of proliferation and/or induction of apoptosis [ 13 ]. Throughout the last decade, several novel therapeutic agents that target siglec-2 are being developed as an alternative approach for cancer treatment [ 17 , 18 , 30 ]. Previous reports showed that siglec-2 as a B-cell-associated adhesion protein appeared to play a critical role in establishing signaling thresholds for B-cell activation, mediating normal antibody response to thymus-independent antigens and regulating the lifespan of mature B cells [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%